RESEARCH ON THE FACTORS THAT INFLUENCE ON SUSTAINABLE CONSUMER BEHAVIOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the modern economic conditions of digitalization and the use of artificial intelligence, consumers do not buy the product, but the expected benefit of this product in the consumption process, or the properties that the product possesses, created in the production process and realized in the consumption process. In the process of making a purchase decision, consumer behavior is influenced by many factors that are inherently factors from the surrounding environment, and others are factors that are the result of the internal attitude of consumers. In order to build and implement a successful marketing strategy, marketing managers should reflect the influence of factors that differ in their characteristics and strength of influence, when the goal is to achieve sustainable consumer behavior of the consumers themselves. By its very nature, the study of the factors themselves represents a special kind of challenge, requiring depth and multi-facetedness from a scientific perspective. The ability to study these factors is a sure indicator for the preparation of a successful strategic marketing strategy that satisfies all stakeholders.